Legal Aspects of Joint Venture Business in The Development of Sustainable Environmental Commercial Property Areas - Putu Sintha Devi Ayudya Ningrat; Deli Bunga Saravistha; Kadek Dedy Suryana (Sociological Jurisprudence Journal, 2025)
Property investment in Indonesia continues to experience significant growth each year, especially through joint venture schemes between domestic and foreign investors. This investment model is considered promising due to high market demand and stable land value appreciation. However, the development of commercial property areas often has an impact on the environment, such as land conversion, social changes in local communities, and potential pollution. Therefore, environmental sustainability aspects have become an important concern in business law, particularly in the regulation of joint venture-based investments. This research aims to examine the legal regulations regarding joint ventures in the development of commercial property areas, as well as the obligation to prepare an Environmental Impact Assessment (AMDAL) as stipulated in national legislation and international principles such as the Rio Declaration 1992, using normative research methods and a case approach. The study results show that although joint ventures are not explicitly regulated in the Limited Liability Company Law, this form of business entity is widely used and subject to environmental legal obligations, including the precautionary principle, polluter pays principle, and sustainable development. This study emphasizes the need for synergy between developers, the government, and the community to ensure that property development is not only economically beneficial but also responsible towards environmental sustainability.